Pelatihan penerapan pembelajaran âPAIKEMâ Bagi Guru Sekolah Dasar Muhammadiyah di Desa Randu, Kec. Subah, Kab. Batang Tahun 2010 - Abidin, Zaenal (Universitas Muhammadiyah Surakarta, 2010)
Learning is an urgent issue in educating nations, to build natonal character, and to set up the noble moral. This clearly defined in the function and the objective ofnational education, that the national education functioned to develop the ability, tobuild character, and to raise the value of national civilization in order to brightennational life. Its goal is to develop the potential of the student in order to be a faithfuland pious person toward God the One, to have the good moral, to be healthy, learned,be capable, creative, autonomous, and to become a democrative and responsiblecitizen.Desa Randu, Kecamatan Subah is the supportive area in Kabupaten Batang. Desa Randu is one of the Branch of Muhammadiyah which quite progressive in Kecamatan Subah, but most of the school development in Kecamatan Subah not welldeveloped yet.In order to fulfill the need, so it necessary to held a training and teaching practices in Microteaching that conditioned as the active learning to the teacher especially the private teachers (Muhammadiyah) with the materials designed by and for the teacher in Teaching and Learning Process.The method used to realizationing this program is in form of training to design PAIKEM Learning (Active, innovative, creative, effective, and exciting) for teacherin SMP Darul Hijrah Desa Randu, Kecamatan Subah Kabupaten Batang.After training, the teacher feel the benefit of participative learning model alsothey feel happy about the training.